Antidiabetic activity of alcoholic root extract of Caesalpinia digyna in streptozotocin-nicotinamide induced diabetic rats - Kumar R.; Patel D.K.; Prasad S.K.; Sairam K.; Hemalatha S. (My University, 2025)
Objective: The present investigation deals with evaluation of antidiabetic (Type 2) activity of standardized alcoholic root extracts of Caesalpinia digyna in STZ-nicotinamide induced diabetic rats. Methods: Alcoholic root extract of Caesalpinia digyna (ACD), obtained from Soxhlet extractor was standardized by HPLC. Type 2 diabetes was induced by single intraperitoneal injection of nicotinamide (110 mg/kg) followed by streptozotocin (65 mg/kg). Diabetic rats ware administered ACD at doses of 250, 500, and 750 mg/kg (p.o.) and different parameters such as normoglycemic and oral glucose tolerance test were evaluated. The study also included estimations of blood plasma glucose, lipid profile, liver glycogen, body weight and anti-oxidant status in normal and diabetic rats. Results: Normoglycemic rats did not reduce the blood glucose level, whereas oral glucose tolerance test showed better tolerance of glucose in treated rats. The alcoholic extract showed a dose dependent reduction in fasting blood glucose level i.e. more pronounced at 750 mg/kg (P<0.05). ACD showed significant reduction in plasma lipid like triglycerides, total cholesterol and improvement in high density lipo-protein cholesterol (HDL-C) in treated groups. The decrease in lipid peroxides and increase in superoxide dismutase (SOD) and catalase (CAT) in liver clearly showed the antioxidant potential while rat hemi-diaphragm glucose uptake study revealed increases in peripheral glucose uptake of treated rats. Conclusions: Results showed that standardized alcoholic extract of C. digyna possessed significant antidiabetic activity which may be attributed to increase in glycogen storage, hypolipidemic and antioxidant activity thus, rationalizing its traditional use. © 2012 Asian Pacific Tropical Biomedical Magazine.